2011
DOI: 10.1007/s12149-011-0468-0
|View full text |Cite
|
Sign up to set email alerts
|

Limited diagnostic and predictive values of dual-time-point 18F FDG PET/CT for differentiation of incidentally detected thyroid nodules

Abstract: The dual-time-point (18)F FDG PET/CT is not a useful method for differentiating malignant and benign nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
13
1
1
Order By: Relevance
“…Most of the 22 patients with malignancies had primary thyroid carcinomas (20 papillary carcinotients with non-thyroid cancer was 8.4%, which was similar to the 9% reported in a previous study that investigated both focal and diffuse 18 F-FDG uptake lesions in thyroid gland (3). The incidence of thyroid incidentalomas (focal lesions) was 5.3% in our study, which was slightly higher than the 1.2−4.3% in other reports in both patients with malignancies and healthy subjects (8)(9)(10)(11). It seemed that this difference resulted from the population in the present study, which included only patients with nonthyroidal malignancies, and previous studies.…”
Section: Discussioncontrasting
confidence: 81%
“…Most of the 22 patients with malignancies had primary thyroid carcinomas (20 papillary carcinotients with non-thyroid cancer was 8.4%, which was similar to the 9% reported in a previous study that investigated both focal and diffuse 18 F-FDG uptake lesions in thyroid gland (3). The incidence of thyroid incidentalomas (focal lesions) was 5.3% in our study, which was slightly higher than the 1.2−4.3% in other reports in both patients with malignancies and healthy subjects (8)(9)(10)(11). It seemed that this difference resulted from the population in the present study, which included only patients with nonthyroidal malignancies, and previous studies.…”
Section: Discussioncontrasting
confidence: 81%
“…Various studies have considered different criteria for PET positivity; ranging from any focal increased uptake in the region of the thyroid nodule above background [11], [12], [17], [18] to different SUVmax cut-offs ranging from 2 to 7 [13], [15], [20], [21]. However, some studies did not find a SUVmax cut-off to be a definite predictor for malignancy [22]. Area under SUVmax curve >175.5 or the heterogeneity factor of FDG uptake >2.751 have also been considered to define FDG-PET positivity [16], [23].…”
Section: Discussionmentioning
confidence: 99%
“…But there was no significant difference in SUVmax of the initial image (SUV1) between the two groups. Kim et al [34] previously reported that dual-time-point 18 F-FDG PET/CT was not a useful method for differentiating malignant and benign nodules through an analysis of a total of 50 patients. They found no statistical differences of dual-phase PET parameters (SUV1, SUV2, and RI) between benign and malignant thyroid lesions.…”
Section: Discussionmentioning
confidence: 99%